Abrasive wear of 2124Al-SiC composites in the temperature range 20-200°C - Muratoglu, M; Aksoy, M (Elsevier Science Sa, 2006)
The main aim of this research was to investigate the influence of temperature (in the range 20-200 degrees C) on the abrasive wear behaviour of a 2124 Al/SiC composite produced by powder metallurgy techniques. Abrasive wear tests were conducted at constant distance and I ON load using pin-on-disk apparatus. Some specimen taken from the composite materials were artificially aged (T6) to determine ageing effects. At the last stage of the study, worn surfaces and the subsurfaces were examined by using SEM, EDS and optical microscopy. Wear test results obtained at all test temperatures showed that the weight loss of the aged specimens was less than that of the non-aged specimens. It was also observed that the better wear resistance was seen for specimens worn at RT both the aged and non-aged specimens. There was no (or little) net change in wear rate for the test temperature above 50 degrees C both the aged and non-aged specimens. Because of contact between SiC particles in the composite material and abrasive paper, broken or loosened hard SiC particulates embedded to the soft layer under worn surface which observed at 50-200 degrees C, caused an increase in strength of surface of the composite specimens and so resulted little change in wear rate. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: metal matrix composite; abrasive wear; temperature